A proposed value-based software process tailoring framework - Zakaria, Noor Azura; Ibrahim, Suhaimi; Mahrin, Mohd Nazri (Institute of Electrical and Electronics Engineers Inc., 2016)
Software process tailoring is the act of customising the existing software process to suit the specific software project. Current practices in software process tailoring consider project characteristics as the sole input to tailor the software process. In addition, it maintains the traditional approach whereby all the project characteristics factors are treated as being equally important. There is a need to shift the traditional software process tailoring approach to a value-centric approach by using a value-based software engineering concept. This study aims to propose a value-based software process tailoring framework to tailor the software process. A review was conducted to analyse the components embedded and input factors in the selected prior studies on software process tailoring. The framework proposed in this study uses value-based factors as input factors to tailor the software process. The framework also considers value prioritisation component, which rank the process elements according to value priority.